The Use of Genre-Based Approach (GBA) to Improve Students' Writing Skill at STIT Palapa Nusantara Lombok - Umar Bakri (Pendidikan Al-Gafari, 2026)
Writing is a productive skill that requires students to generate ideas, organize them into a meaningful text, and apply appropriate language features. However, students at STIT Palapa Nusantara Lombok still experience difficulties in writing English texts, especially descriptive texts, due to limited vocabulary, weak control of grammar, and lack of systematic writing guidance. This study aimed to improve students’ writing skill through the implementation of the Genre-Based Approach (GBA). The research design was Classroom Action Research conducted in two cycles involving 35 students. Data were collected through observation, writing tests, and documentation. The data were analyzed using both qualitative and quantitative approaches. The results showed that students’ writing performance improved significantly after the implementation of GBA. The mean score increased from 58.28 in the preliminary test to 81.03 in Cycle I and improved to 83.79 in Cycle II. In Cycle II, all students achieved the minimum mastery criterion (70). The classroom observation also indicated better student engagement, collaboration, and confidence in composing descriptive texts. Therefore, GBA is effective in improving students’ writing skill at STIT Palapa Nusantara Lombok.